71‐4: Uniformity Study on High Resolution OLED Display Fabricated by Ink Jet Printing Process. Issue 1 (May 2017) - Chen, Peng-Yu; Chen, Chien-Chuan; Hsieh, Cheng-Chin; Lin, Yu-Syuan; Li, Chun-Han; Lin, Yu-Hsin; Hong, Hong-Jye
Abstract : In this work, the emission uniformity from the pixels in an OLED display fabricated by ink jet printing was studied. First, the process parameters such as vacuum dry speed and vacuum dry temperature were controlled. Second, a new pixel fusion design was used to improve uniformity. The pixel resolution in our study was 167ppi, which met the requirement for automotive vehicle application. We demonstrated that the film quality of produced from ink jet printing can meet the demand of commercial products.